Features of application of single- and multi-component terms in the Kazakh official style - Rapisheva, Zh.D. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
The article discusses the terms used at the present stage in the official sphere, among which are the terms and term combinations derived from the native Kazakh words. The authors of the article emphasize that today the process of transferring the names of new concepts and phenomena in the native language by reproducing the meaning of the word, using word-forming forms, as well as ways of combining, combining words in the native language, terminology in this area is not only one-two-component, but also three to four, five to six components. An analysis of the methods for the formation of legal terms showed that legal terms consist of own and borrowed words, in terms of grammatical structure they are often one-component, and multi-component terms are currently used more often than in previous periods in the development of this style.
Қазақ ресми стиліндегі бір және көпкомпонентті терминдердің қолданылу ерекшеліктері
Особенности употребления одно- и многокомпонентных терминов в казахском официальном стиле
Keywords: term; term combination; official style; complex terms; one-component term; multi-component term; office work terms; terminological system; codification of terms